1999
DOI: 10.1046/j.1432-1327.1999.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of CcEcR

Abstract: In order to understand the role that 20-hydroxyecdysone plays during development of the Mediterranean fruit fly Ceratitis capitata (medfly), a major agricultural pest, we have cloned a Ceratitis ecdysone receptor (CcEcR) and studied its expression and its binding properties to an ecdysone response element. Using the conserved DNA binding region of the Drosophila melanogaster ecdysone receptor (DmEcR) B1 cDNA as a probe, we isolated a medfly cDNA clone containing the coding region, a part of the 5 H -untranslat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 57 publications
3
20
0
3
Order By: Relevance
“…DmEcR, CfEcR, BaEcR, and BmEcR are underlined as their proteins contain a Tyr at the critical ligand specificity site. Data bank search yielded EcR protein sequences from 16 species: 6 Diptera species, the Mediterranean fruit fly Ceratitis capitata (CcEcR [67]), the sheep blowfly Lucilia cuprina (LcEcR [23]), the yellow fever mosquitoes A. aegypti (AaEcR, 12) and A. albopictus (not shown, as its EcR I box is 100% identical to AaEcR [28]), the midge Chironomus tentans (CtEcR [27]), and D. melanogaster (DmEcR [34]); 6 Lepidoptera species, the spruce budworm C. fumiferana (CfEcR [35]), squinting bush brown Bicyclus anynana (BaEcR [R. K. Reinhardt, P. Weber, and P. B. Koch, submitted to GenBank, accession no. CAB63236]), the silkworm B. mori (BmEcR [32,60]), the tobacco budworm Heliothis virescens (HvEcR [41]), the tobacco hornworm M. sexta (MsEcR [18]), and the buckeye Junonia coenia (JcEcR [R. K. Reinhardt, P. Weber, and P. B. Koch submitted to GenBank, accession no.…”
Section: Discussionmentioning
confidence: 99%
“…DmEcR, CfEcR, BaEcR, and BmEcR are underlined as their proteins contain a Tyr at the critical ligand specificity site. Data bank search yielded EcR protein sequences from 16 species: 6 Diptera species, the Mediterranean fruit fly Ceratitis capitata (CcEcR [67]), the sheep blowfly Lucilia cuprina (LcEcR [23]), the yellow fever mosquitoes A. aegypti (AaEcR, 12) and A. albopictus (not shown, as its EcR I box is 100% identical to AaEcR [28]), the midge Chironomus tentans (CtEcR [27]), and D. melanogaster (DmEcR [34]); 6 Lepidoptera species, the spruce budworm C. fumiferana (CfEcR [35]), squinting bush brown Bicyclus anynana (BaEcR [R. K. Reinhardt, P. Weber, and P. B. Koch, submitted to GenBank, accession no. CAB63236]), the silkworm B. mori (BmEcR [32,60]), the tobacco budworm Heliothis virescens (HvEcR [41]), the tobacco hornworm M. sexta (MsEcR [18]), and the buckeye Junonia coenia (JcEcR [R. K. Reinhardt, P. Weber, and P. B. Koch submitted to GenBank, accession no.…”
Section: Discussionmentioning
confidence: 99%
“…Amino-acid sequences Identity(%) (Verras et al, 1999), 1-MMKRRWSNNGG-11 Lucilia cuprina (Hannan et al, 1997), 1-MMKRRWSNNGG-11 Aedes albopictus (Jayachandran and Fallon, 2000) 1-MMKRRWSNNGG-11 Aedes aegypti (Cho et al, 1995) 1-MR-RRWSNNGG-10 Choristoneura fumiferana (Perera et al, 1999) …”
Section: Insectmentioning
confidence: 99%
“…insect origins. The N-terminal 10 amino-acid residues "M(M/ R)(K/-)RRWSNNGG" are well conserved among 12 insect species [Ceratitis capitata (Verras et al, 1999), Lucilia cuprina (Hannan et al, 1997), Plodia interpunctella (Siaussat, et al, 2004), Aedes albopictus (Jayachandran et al, 2000), Aedes aegypti (Cho et al, 1995), Choristoneura fumiferana (Perera et al, 1999), Chilo suppressalis (Minakuchi, et al, 2002), Manduca sexta, (Fujiwara et al, 1995), Bombyx mori (Hossain et al, 2006), Leptinotarsa decemlineata (Ogura et al, 2005), Spodoptera frugiperda (Chen et al, 2002) and Drosophila melanogaster (Koelle et al, 1991)], all of the insect species from which EcR-B1 isoforms have been identified (Table 2). We then examined whether this sequence was encoded between exons 2 and 3 of AmEcR, where the exon for the B1 isoform, if any, was expected to exist.…”
Section: Fig 2 Northern-blot Analysis Of Amecr-amentioning
confidence: 99%
“…These data (Kothapalli et al, 1995)], Cs [Chilo suppressalis (Minakuchi et al, 2002)], Pi (Plodia interpunctata, Accession no. AAR84611), Cc [Ceratitis capitata (Verras et al, 1999)], Dm [Drosophila melanogaster (Koelle et al, 1991)], Lc [Lucilia cuprina (Hannan and Hill, 1997)], Ae [Aedes aegypti (Cho et al, 1995)], Ct [Chironomus tentans (Imhof et al, 1993)], Hv [Heliothis virescens (Martinez et al, 1999)], Ms [Manduca sexta (Fujiwara et al, 1995)], Bm [Bombyx mori (Kamimura et al, 1996;Swevers et al, 1995)], Lm [Locusta migratoria EcR (Saleh et al, 1998)], Tm [Tenebrio molitor EcR (Mouillet et al, 1997)], Mp [Myzus persicae (Hill, 1999)], Up [fiddler crab Uca pugilator (Chung et al, 1998)], Ama [ixodid tick Amblyomma americanum (Guo et al, 1997)]. …”
Section: April 2005mentioning
confidence: 99%